A Non-Linear Association of Triglyceride Glycemic Index With Cardiovascular and All-Cause Mortality Among Patients With Hypertension - Zhou, Dan; Liu, Xiao-cong; Kenneth, Lo; Huang, Yu-qing; Feng, Ying-qing (Frontiers in Cardiovascular Medicine, 2022)
Background To investigate the association between Insulin resistance (IR), quantified by Triglyceride glycemic index (TyG index), and Cardiovascular mortality (CVM), All-cause mortality (ACM) in hypertension patients. Methods We included 8554 hypertension patients aged ≥18 years old from the 1999–2014 National Health and Nutrition Examination Surveys (NHANES). The status of CVM and ACM of participants were followed through 31 December 2015. Cox proportional hazards models and Kaplan-Meier survival curves were used to evaluate the relationship between TyG index and CVM, ACM. Results During a median of 82 months follow up, 1882 mortality cases had occurred, 434 mortality cases due to cardiovascular disease. The hypertension patients with TyG ≥10 was older, more smokers, obesity, higher blood pressure, more cardiovascular disease. In Cox proportional hazards models, compared with the patients with TyG<8, those with TyG ≥10 had 56% risk increased for ACM, no significant difference for CVM between the four group. In the restricted cubic spline regression models, the relationship between TyG index and ACM was nonlinear. Subgroup analysis showed nonlinear relationship between TyG index and ACM in elderly patients with aged ≥60 years. The cut-off value of TyG for ACM was 9.45, higher or lower than 9.45 had more risk of ACM. When TyG index was more than 9.52, the risk for CVM would increase among the whole group. Kaplan-Meier survival curves showed patients with TyG ≥10 had higher risk of ACM and CVM (Log rank P <0.05). Conclusions we demonstrated that the association was nonlinear between ACM and TyG index in elderly hypertension with aged ≥60 years. However, TyG index was only more than 9.52, the risk for CVM would increase among the whole hypertension group.